Analisis Hukum Penelantaran Tanah Girik dan Pembuatan Sertifikat Oleh Pihak Lain Serta Upaya Penyelesaian Sengketanya - Gemilang, Kharisma (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to find out what factors cause the large number of Girik lands to be abandoned by their owners and can be certified by other parties, to find out the legal status of abandoned Girik lands when they have been certified by other parties, and to find out the efforts to resolve disputes over Girik lands which have been certified by other parties. other. For this reason, the research method used is a type of qualitative research using a descriptive analysis method which applies a literature study approach accompanied by observations of something that happens in society. There are many factors that have caused this neglected land to be certified by other parties, because it has been neglected, because land administration has been less orderly, because of legal uncertainty. Awareness for landowners to cultivate their land and legal certainty in matters of land is urgently needed.